Carbon quantum dot sensitized Pt@Bi2WO6/FTO electrodes for enhanced photoelectro-catalytic activity of methanol oxidation. Issue 43 (22nd May 2017) - Zheng, Huajun; Niu, Ping; Zhao, Zhefei
Abstract : Carbon quantum dots (CQDs) sensitized Pt@Bi2 WO6 /FTO electrodes (simplified as CQDs-Pt@Bi2 WO6 /FTO) were prepared by loading platinum particles onto Bi2 WO6 nanoplates via a photo-deposition method and sensitized CQDs via a dip-coating method. Abstract : Carbon quantum dot sensitized Pt@Bi2 WO6 /FTO electrodes (simplified as CQDs-Pt@Bi2 WO6 /FTO) were successfully prepared by loading platinum particles onto Bi2 WO6 nanoplates via a photo-deposition method and sensitized carbon quantum dots (CQDs) via a dip-coating method. The photoelectro-catalytic properties of the Pt@Bi2 WO6 /FTO and CQDs-Pt@Bi2 WO6 /FTO electrodes for methanol oxidation were investigated. The results indicated that the CQDs-Pt@Bi2 WO6 /FTO electrode shows higher photoelectro-catalytic activity and better stability than that of the Pt@Bi2 WO6 /FTO electrode. The higher photoelectro-catalytic performance for methanol oxidation was attributed due to the special synergetic effects between the photocatalytic and electrocatalytic process under solar light irradiation. More importantly, the introduction of CQDs broaden the photoresponse range of the Bi2 WO6 material and improves the mobility of the photocarriers. Meanwhile, the doped CQDs act as preferential adsorption sites for the intermediate carbonaceous species during methanol oxidation. This not only alleviates CO poisoning towards the Pt particles, but also improves the efficiency of methanol oxidation by constructing a new type of CQDs-Pt electrocatalyst. The composite material, which combines the dual function of photocatalysis and electrocatalysis will be a promising candidate for new photoelectro-catalytic fuel cells.